(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. Nagari Sungai Nyalo Mudiak Aia is administratively included in the Koto XI sub-district of Tarusan Selatan Pesisir Selatan Regency. One of the villages included in the list of villages in rural areas is a national priority. It takes 75 minutes to get to the location from the Regency capital and 120 minutes from the provincial capital. One of the destinations that are located in the kenagarian Sungai Nyalo Mudiak Aia is Bukit Batu Garudo. Based on the SWOT analysis, it can be concluded specifically the problem in the Batu Garudo Kenagarian Sungai Nyalo was there is no management of special interest tourism trekking to Batu Garudo, lack of human resources who have expertise/certification in the field of trekking and outbound scout-ing. The target audience in this community service activity are young people in the Sungai Nyalo region. The purpose of this activity is the existence tourist destination with the concept “Bukit Batu Garudo Adventure Trekking (The Real View of Paradise)” The method used is counseling, training, workshops and workshops as well as mentoring. The solution is to create, develop and organize destinations for tourists in special interest activities. Solutions are given training management of trekking management activities, and given in the form of training on good camping guides. The results obtained are the existence of trekking paths along with the track facilities and activities carried out, understanding of the management of trekking recreation areas, and the existence of trekking guides from the Sungai Nyalo tourism awareness group. Abstrak. Nagari Sungai Nyalo Mudiak Aia secara administratif termasuk dalam wilayah Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan. Salah satu desa yang termasuk dalam daftar desa pada kawasan perdesaan prioritas nasional. Waktu tempuh menuju pusat kota kecamatan sekitar 75 menit sedangkan waktu tempuh menuju ibukota kabupaten kira-kira 120 menit. Salah satu destinasi wisata yang terletak di kenagarian Sungai Nyalo Mudiak Aia adalah Bukit Batu Garudo (Baga). Berdasarkan analisis SWOT dapat disimpulkan secara khusus permasalahan di Batu Garudo Kenagarian Sungai Nyalo adalah belum adanya pengelolaan wisata minat khusus trekking ke Batu Garudo, minimnya tenaga SDM yang memiliki keahlian/sertifikasi di bidang kepemanduan trekking dan outbound. Khalayak sasaran dalam kegiatan pengabdian ini adalah para pemuda di kenagarian Sungai Nyalo. Adapun tujuan dari kegiatan ini adalah terciptanya sebuah destinasi wisata trekking dengan konsep “Bukit Batu Garudo Adventure Trekking (The Real View Of Paradise). Metode yang digunakan adalah penyuluhan, pelatihan, workshop dan lokakarya serta pendampingan. Adapun solusi adalah pembuatan, pengembangan dan penataan wisata minat khusus trekking ke Batu Garudo, pelatihan manajemen pengelolaan kegiatan trekking, dan pelatihan tentang memandu camping yang baik. Hasil yang didapat adalah Adanya jalur trekking beserta dengan fasilitas jalur dan kegiatan yang dilaksanaka, Adanya pemahaman manajemen pengelolaan tempat rekreasi trekking, lahirnya pemandu trekking dari kelompok sadar wisata Sungai Nyalo.